The association between obstructive sleep apnea severity and sleep architecture measured with non-contact radar technology in primary investigation and follow-up on therapy: A pilot study. - Vigdis Fossland; Ståle Toften; Ingrid Kathrin Hals; Hege S Haugdahl; Ole Kristian Thu; Hanne Sorger (PLoS ONE)
Purpose The purpose of this pilot study was to investigate if sleep classification data from a non-contact sleep monitor placed in the patient's bedroom at home were associated with obstructive sleep apnea (OSA) severity at the time of primary investigation. Secondly, we aimed to study the effect of established continuous positive airway pressure (CPAP) therapy on objective sleep classification measurements. Methods We performed a prospective single center study at a medium size hospital. Adult patients referred with symptoms that could indicate OSA underwent standard respiratory polygraphy (RPG) registration, sleep classification measured with non-contact radar technology (Somnofy, Vitalthings AS, Norway), and answered the Epworth Sleepiness Scale (ESS) questionnaire. After 12-20 weeks, ESS and non-contact registration was repeated in patients diagnosed with OSA who had eslished effective CPAP therapy. Results A total of 47 patients (62% men, mean age 51 years) were diagnosed with OSA based on the respiratory event index (REI). OSA severity correlated negatively with total sleep time (p <  0.003), fraction of deep and REM sleep (p <  0.000 and p <  0.036, respectively), and positively for sleep fragmentations (p <  0.007), recorded by the Somnofy. After CPAP therapy, patients slept longer in total (p <  0.012), with more deep sleep (p <  0.001) and less sleep fragmentation (p <  0.009). Although OSA severity correlated with sleep classification data, there was no association with self-reported symptoms (ESS) at baseline or during CPAP therapy. Conclusion We demonstrated that non-contact sleep measurements in a home environment seem to correlate with OSA severity and could be a valuable supplement to RPG and ESS in OSA diagnosis and follow up on therapy.